Carbon Dioxide Capture from Ambient Air Using Amine-Grafted Mesoporous Adsorbents. (28th April 2013) - Wagner, Annemarie; Steen, Bengt; Johansson, Göran; Zanghellini, Ezio; Jacobsson, Per; Johansson, Patrik
Abstract : Anthropogenic emissions of carbon dioxide (CO2 ) have been identified as a major contributor to climate change. An attractive approach to tackle the increasing levels of CO2 in the atmosphere is direct extraction via absorption of CO2 from ambient air, to be subsequently desorbed and processed under controlled conditions. The feasibility of this approach depends on the sorbent material that should combine a long lifetime with nontoxicity, high selectivity for CO2, and favorable thermodynamic cycling properties. Adsorbents based on pore-expanded mesoporous silica grafted with amines have previously been found to combine high CO2 adsorption capacity at low partial pressures with operational stability under highly defined laboratory conditions. Here we examine the real potential and functionality of these materials by using more realistic conditions using both pure CO2, synthetic air, and, most importantly, ambient air. Through a combination of thermogravimetric analysis and Fourier transform infrared (TGA-FTIR) spectroscopy we address the primary functionality and by diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy the observed degradation of the material on a molecular level.